2014
DOI: 10.1111/dme.12422
|View full text |Cite
|
Sign up to set email alerts
|

Impact of socio‐economic status on breast cancer screening in women with diabetes: a population‐based study

Abstract: The presence of diabetes was an independent barrier to breast cancer screening, which was not explained by differences in socio-economic status. Interventions that target patient, provider, and health system factors are needed to improve cancer screening in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
(52 reference statements)
0
30
1
Order By: Relevance
“…Previous studies have found that diabetes poses a significant barrier to adequate breast cancer screening . Our group has shown that women with diabetes are less likely to undergo screening mammography than those without diabetes, even within the Ontario Breast Cancer Screening Program . However, this study did not show a similar trend for diagnostic testing once women were screened.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Previous studies have found that diabetes poses a significant barrier to adequate breast cancer screening . Our group has shown that women with diabetes are less likely to undergo screening mammography than those without diabetes, even within the Ontario Breast Cancer Screening Program . However, this study did not show a similar trend for diagnostic testing once women were screened.…”
Section: Discussioncontrasting
confidence: 77%
“…Evidence suggests that women with diabetes are more likely to be diagnosed with postmenopausal breast cancer, present at an advanced stage, and have increased all-cause mortality after being diagnosed with breast cancer, compared to women without diabetes [1][2][3][4][5][6]. Although effective screening has been shown to decrease breast cancer mortality in postmenopausal women, those with diabetes are less likely to undergo regular mammograms [7][8][9][10][11]. Even if a screening mammogram is performed, an abnormal test needs to be followed-up in a timely ORIGINAL RESEARCH Time to follow-up of an abnormal mammogram in women with diabetes: a population-based study manner in order for the screening to be considered effective.…”
Section: Introductionmentioning
confidence: 99%
“…However, women with diabetes are less likely to be up-to-date compared to men with diabetes. Further, women with diabetes tend to participate less in clinical preventive services (i.e., mammography screening) compared to women without diabetes ( 35 ). We did not specifically evaluate interactions between patient characteristics, but important subgroups, such as overweight women with diabetes could be potential target populations for screening outreach.…”
Section: Discussionmentioning
confidence: 99%
“…[911]. Some studies demonstrate that individuals with existing co-morbidities, such as diabetes, have lower cancer screening rates than those without co-morbidities[1214]; and in some cases, those with diabetes have lower screening rates despite having more visits to healthcare providers [9, 15–17]. A proposed reason for this under-screening includes competing priorities, i.e.…”
Section: Introductionmentioning
confidence: 99%